Calming the emotional storm : using dialectical behavior therapy skills to manage your emotions & balance your life - Van Dijk, Sheri (Oakland, CA : New Harbinger Publications, 2012)
Dialectical behavior therapy (DBT) is a therapeutic modality that was originally developed for the treatment of borderline personality disorder (BPD). Since the advent of this therapy, millions of people without the disorder have found DBT skills endlessly useful for helping manage out-of-control emotions and curbing impulsive behaviors that they just can't stop. "Calming the Emotional Storm" is the first book to offer an accessible, general introduction to these DBT skills for anyone who feels overwhelmed by their emotions or feels that their emotions have led them to experience out-of-control behaviors and personal crises. Readers learn to understand and manage their emotions and begin to choose their actions rather than acting on impulses. They also practice calming their emotions in times of stress by embracing acceptance and fostering positive emotions about themselves. These life-changing skills can save many readers from unnecessary suffering due to the "emotional storm" inside.
Introduction -- Mindfulness : seeing things as they are -- Don't just react : choose how to act -- Learning about your emotions -- Quieting your emotions -- Leave the judgments out of it -- Uncorrected proof -- Calming the emotional storm -- How to be more effective in your life -- Getting through a crisis without making it worse -- Accepting things as they are -- The building blocks for positive emotions -- Improving your relationships -- Conclusion -- References.
Formerly CIP.
Includes bibliographical references.
Keywords: Emotions; Dialectical behavior therapy